A blend of essential oils improved feed efficiency and affected ruminal and systemic variables of dairy cows. Issue 1 (31st December 2019) - Silva, Rayana Brito da; Pereira, Marcos Neves; Araujo, Rafael Canonenco de; Silva, Wesley de Rezende; Pereira, Renata Apocalypse Nogueira
Abstract: This experiment evaluated the effect of a blend of essential oils (BEO ) on intake, lactation performance, diet digestibility, ruminal fermentation profile, eating behavior, body thermoregulation, blood acid–base balance, and milk fatty acid profile of lactating cows. Twenty-eight Holstein cows were individually fed a standard diet for 14 d and treatments control or BEO (a microencapsulated blend of pepper extract containing capsaicin and pure forms of carvacrol, cinnamaldehyde, and eugenol; 150 mg/kg of diet dry matter) for 56 d. Significance was declared at P ≤ 0.05 and trends at 0.05 < P ≤ 0.10. Dry matter intake (DMI ) was reduced (19.5 vs. 20.1 kg/d) and milk yield was increased (30.1 vs. 30.8 kg/d) by BEO, inducing improved milk to DMI ratio (1.53 vs. 1.62). Milk fat concentration tended to be increased by BEO, but total solids yield did not differ. There was a trend for increased total tract non-neutral detergent fiber organic matter digestibility with BEO. The molar proportion of acetate in ruminal fluid was reduced (51.4 vs. 57.8%) and that of propionate was increased (26.1 vs. 31.3%) by BEO. Ruminal microbial yield and total protozoa count in ruminal fluid did not differ. Cows fed BEO ingested a greater proportion of the daily intake in the morning (30.6 vs. 36.6%) and tended to ingest a lower proportion at night, tended to have longer meals, and had fewer meals per day (11.9 vs. 13.7) and larger meal size (1.5 vs. 1.7 kg of dry matter per meal). Blood urea-N and glucose concentrations did not differ. The BEO increased jugular blood oxygenation. The sweating rate on a hot and dry day was increased (160 vs. 221 g/m 2 /h) by BEO. The mean rectal and skin temperatures and respiration rate did not differ, but the proportion of rectal temperature measurements ≥39.2 °C was reduced by BEO at 1400 h (17.8 vs. 28.5%) and 2000 h (23.2 vs. 34.8%). The BEO increased the secretion (g/d) of 18:2 trans -10, cis -12 and the concentration of 18:0 iso fatty acids in milk fat. When one sample of milk from BEO cows was offered with two samples of milk from control, 59% of regular consumers of milk ( n = 63) identified the odd sample correctly. The gain in feed efficiency induced by BEO was associated with reduced acetate-to-propionate ratio in ruminal fluid, altered eating behavior, lower frequency of high rectal temperature, and increased blood oxygenation. Essential oils had positive effects on ruminal fermentation and systemic variables of dairy cows.